2020
DOI: 10.2138/am-2020-7236
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic SiO2-cristobalite: A natural product of chemical vapor deposition

Abstract: Cristobalite is a low-pressure, high-temperature SiO2 polymorph that occurs as a metastable phase in many geologic settings, including as crystals deposited from vapor within the pores of volcanic rocks. Such vapor-phase cristobalite (VPC) has been inferred to result from silica redistribution by acidic volcanic gases but a precise mechanism for its formation has not been established. We address this by investigating the composition and structure of VPC deposited on plagioclase substrates within a rhyolite lav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
3
25
0
Order By: Relevance
“…2). The linear features are also consistent with dislocations imaged by APT in other minerals (Piazolo et al, 2016;Kirkland et al, 2018;Fougerouse et al, 2019;Schipper et al, 2020). Trace-element enrichment in the dislocation is up to 3.2 at% increase, including Ni, Cu, As, Pb, Sb, Bi, and Au (Table 1).…”
Section: Trace Element-enriched Crystal Defectssupporting
confidence: 81%
“…2). The linear features are also consistent with dislocations imaged by APT in other minerals (Piazolo et al, 2016;Kirkland et al, 2018;Fougerouse et al, 2019;Schipper et al, 2020). Trace-element enrichment in the dislocation is up to 3.2 at% increase, including Ni, Cu, As, Pb, Sb, Bi, and Au (Table 1).…”
Section: Trace Element-enriched Crystal Defectssupporting
confidence: 81%
“…cations other than Si (Holmquist, 1961;Roy & Roy, 1964;Dapiaggi et al, 2015). This is consistent with Crs in volcanic products having > 1 wt% Al2O3 (up to ~3 wt%) and significant alkali (especially Na2O) contents (Pallister et al, 2008;Horwell et al, 2012;Schipper et al, 2015Schipper et al, , 2020Ivanova et al, 2018), whereas Qtz generally hosts < 1 wt% Al2O3 (Pallister et al, 2008;Horwell et al, 2012;Breiter et al, 2012). For Trd, the available data (Pallister et al, 2008) indicate the presence of Al2O3 and Na2O in smaller concentrations than in Crs but in greater concentrations compared to Qtz.…”
Section: Chemistry Of the Silica Polymorphsmentioning
confidence: 55%
“…The analytical errors on major elements were calculated at ~1% (relative) for SiO2, Al2O3 and CaO, and 5% for Na2O. Schipper et al (2020) reported Na migration under the electron beam during cristobalite analyses, as such, we have tested the effect of defocusing the beam under the above conditions. We did not observe differences in Na content between the focused (spot size of 1 µm) and defocused (10x10 µm) beam.…”
Section: Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoscale trace element variations in platinum‐group alloys have also been identified by APT and this has allowed the discrimination of magmatic versus weathering origins for such particles (Parman et al ). Similarly, fine‐scale compositional variations formed during mineral growth, and the subsequent modification of such growth profiles at the nanoscale by diffusion (Bloch et al ), interface‐coupled dissolution–reprecipitation (Peterman et al ) or exsolution (Genareau et al ), could be measured by APT and have the potential to place valuable constraints on magmatic, metamorphic and ore‐related petrogenetic processes (Cao et al , Gamal El Dien et al , Schipper et al ).…”
Section: Geoscience Applicationsmentioning
confidence: 99%